Environment-friendly composite material for improving photovoltaic photoelectric efficiency and preparation method and application thereof
By combining modified titanium dioxide and graphene, the problem of low light absorption and electron transport efficiency in photovoltaic materials has been solved, achieving full-spectrum absorption and efficient electron transport. The materials are environmentally friendly and stable, and are suitable for existing photovoltaic production lines.
Patent Information
- Application Number
- CN202511469329.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-14
- Publication Date
- 2026-01-09
AI Technical Summary
Existing photovoltaic materials cannot synergistically improve light absorption and electron transmission efficiency. Traditional photovoltaic auxiliary materials contain heavy metals/harmful ions and have poor stability. Their morphology/dispersion issues make it difficult to adapt to existing photovoltaic production and application scenarios.
Agent A, consisting of titanium oxide, sodium sulfate, sodium pyrophosphate, and rare earth compounds, is formed by grinding and then nitriding under plasma heating at 2500℃ to create a nitrogen-doped lattice. Agent B, consisting of graphite, polyethylene glycol, sodium sulfate, sodium pyrophosphate, and rubidium-containing soluble ionic salts, is formed by ultrasonic mixing and oxidation to create a carbon atom recombination structure. These agents are used to enhance light absorption and electron transport, respectively.
Significantly improves the photoelectric performance of photovoltaic modules, expands the light absorption range to the full spectrum, enhances electron transport efficiency, improves material stability, adapts to existing production lines, and extends service life.
Smart Images

Figure CN121310787A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of photovoltaic industry, and particularly relates to a preparation method and application of an environmentally-friendly combined material for improving photovoltaic photoelectric efficiency. BACKGROUND
[0002] The photovoltaic industry is currently in a very mature development stage, and the development of new materials for improving light absorption and power generation efficiency is in an extremely active and rapid breakthrough stage. The development goal of photovoltaic technology worldwide is to improve photoelectric conversion efficiency, reduce manufacturing cost, enhance performance and stability, improve service life, and expand application scenarios, etc., so as to further promote the popularization of solar power generation. Currently, the mainstream of the market is the most popular perovskite solar cell, which is developing at a very fast speed. The highest efficiency of perovskite in the laboratory has broken through 26.1%, far exceeding thin-film batteries, and approaching the limit of crystalline silicon (about 26.7%). The efficiency of perovskite / silicon stacked cells has broken through 33.9% (laboratory data), and the theoretical limit can reach more than 45%, indicating the direction for future efficiency improvement.
[0003] Then, the current photovoltaic material pattern is still dominated by crystalline silicon, and perovskite photovoltaic cells are the main research and development direction in the current market, but the current mass production is still based on the crystalline silicon system. Because the shortcomings of the current perovskite material are short service life, mainly organic ammonium, ruxiong ion, organic cation, lead ion, iodine ion, etc., the most common representative is methylamine lead iodine (CH3NH3Pbl3), therefore, the present application mainly uses traditional crystalline silicon material, and uses the material of the present application as an auxiliary material for improving the light absorption and power generation efficiency of traditional crystalline silicon products. The material of the present application has the functions of environmental protection and high efficiency, and will not be harmful to the environment or have certain corrosiveness and instability to the material itself like traditional photovoltaic materials such as ruxiong ion or some lead ion, and focuses on environmental protection and improvement of material performance and service life.
[0004] The traditional crystalline silicon material has high electric conversion efficiency, but low light absorption efficiency, and the light absorption efficiency of perovskite battery is high, but after absorption, it separates into electrons and holes, but the transmission efficiency of holes is lower than that of electrons, thus causing unsmooth transmission and efficiency reduction.
[0005] Traditional titanium dioxide primarily absorbs ultraviolet radiation from sunlight, which accounts for only 5% of the solar spectrum. The rutile absorption band edge of titanium dioxide is approximately 415 nm (3.0 eV), and the anatase absorption band edge is approximately 387 nm (3.2 eV). Its optical bandgap, particularly that of crystalline silicon, is poorly tunable, ranging from 1.12 eV. Therefore, it is mainly compatible with the near-infrared range (600-1100 nm) of the visible to invisible solar spectrum, resulting in limited energy absorption. Commercially available photovoltaic enhancement materials primarily combine the photocatalytic effect of titanium dioxide with silicon dioxide or silica sol to create a material that provides self-cleaning, anti-sticking, hydrophobic, and antistatic properties for photovoltaic glass surfaces. Coatings can only reduce dust on the surface of photovoltaic glass. Traditional photocatalytic titanium dioxide itself has no effect on light sensitivity or light source absorption. Moreover, over time, the performance of the material itself decreases significantly, and its actual contribution to the power generation efficiency of photovoltaic modules is limited. Therefore, it is necessary to nitrid the titanium dioxide to modify the lattice of the material, so as to improve the absorption range of the full spectrum of sunlight. Traditional graphene is a powder material, which cannot be well mixed and produced with photovoltaic module materials. Therefore, it is necessary to modify the material, optimize the production method and material properties, so that the modified graphene material can be more perfectly combined with photovoltaic module materials, improving its overall effects such as electron transmission and heat dissipation. Summary of the Invention
[0006] The purpose of this invention is to provide a method and application for preparing environmentally friendly composite materials to improve photovoltaic photoelectric efficiency, in order to solve the problems in the prior art where photovoltaic core materials cannot synergistically improve light absorption and electron transmission efficiency, traditional photovoltaic auxiliary materials contain heavy metals / harmful ions and have poor stability, and traditional auxiliary materials are difficult to adapt to existing photovoltaic production and application scenarios due to morphology / dispersion issues.
[0007] To achieve the above objectives, the present invention provides the following solution: An environmentally friendly composite material for improving photovoltaic photoelectric efficiency, the composite material is composed of agent A for improving the light absorption efficiency of photovoltaic modules and agent B for improving the electron transmission efficiency of photovoltaic modules; Agent A is titanium oxide, sodium sulfate, sodium pyrophosphate, and rare earth compounds that are ground and then subjected to nitriding treatment under plasma heating at 2500℃ with nitrogen gas to form a nitrogen-doped lattice, which is then dissolved in deionized water and nano-grinded to obtain the product. The rare earth compound is a rare earth chloride or a rare earth acetate compound. The agent B consists of graphite, polyethylene glycol, sodium sulfate, sodium pyrophosphate, a rubidium-containing soluble ionic salt, and sulfuric acid. After ultrasonic mixing and oxidation, a graphite product is formed, with a concentration ≤10. -6The carbon atom recombination structure is formed by heating at 1300℃ under ultra-vacuum and then being discharged in an electric arc furnace at 3500℃. Finally, it is dissolved in isopropanol and then prepared by nano-ultrasonic grinding. The rubidium-containing soluble ionic salt is rubidium chloride or rubidium acetate.
[0008] Preferably, the titanium dioxide in agent A is composed of anatase titanium dioxide and rutile titanium dioxide, and the mass ratio of anatase titanium dioxide to rutile titanium dioxide is 1:1. The titanium dioxide accounts for 1% to 5% of the total mass of agent A.
[0009] Preferably, the rare earth chloride in agent A is lanthanum chloride or europium chloride.
[0010] Preferably, the mass ratio of titanium dioxide, sodium sulfate, sodium pyrophosphate, and rare earth chloride in agent A is 10000:20:25:5.
[0011] Preferably, the mass ratio of graphite, polyethylene glycol, sodium sulfate, sodium pyrophosphate, rubidium chloride, and sulfuric acid in agent B is 10000:50:20:25:5:500.
[0012] Preferably, the mass ratio of isopropanol to graphite product in agent B is 100:0.5-3.
[0013] A method for preparing the aforementioned environmentally friendly composite material for improving photovoltaic photoelectric efficiency includes: S1. Titanium oxide pretreatment: Anatase titanium oxide and rutile titanium oxide are mixed in a mass ratio of 1:1 and ground to 800 mesh to obtain titanium oxide mixed powder; S2. Dispersion and doping: Sodium sulfate, sodium pyrophosphate and rare earth chloride are added to the titanium dioxide mixed powder, dispersed with water and then dried to obtain a dry powder. S3. High-temperature nitriding modification: The dried powder is placed in an electric arc furnace and nitrided by introducing nitrogen gas under plasma heating conditions at 2500℃ to form nitrogen-doped lattice powder. S4. Preparation of finished product: The nitrogen-doped lattice powder is added to deionized water at a ratio of 1% to 5% of the total mass of the final agent A, and then ground to obtain agent A; S5. Graphite pretreatment and oxidation: Add 800-mesh graphite to polyethylene glycol, sodium sulfate, sodium pyrophosphate, rubidium chloride and water, then add sulfuric acid for oxidation, let stand and dry to obtain dry powder; S6. High-temperature recombination: The dried powder is heated to 1300°C under ultra-vacuum conditions of ≤10-6Pa, cooled, placed in an electric arc furnace, and discharged at a temperature above 3500°C to obtain carbon atom recombination powder. S7. Solvent mixing and dispersion of the finished product: The carbon atom recombinant powder is added to isopropanol at a ratio of 0.5% to 3% of the total mass of the final agent B, and then subjected to nano-ultrasonic grinding and ultrasonic dispersion to obtain agent B.
[0014] Preferably, in the nitriding process of step S3, the heat preservation reaction time is 0.8-1.2h.
[0015] Preferably, in step S6, during the discharge process at temperatures above 3500°C, the discharge time is 25-35 minutes.
[0016] An application of an environmentally friendly composite material for improving photovoltaic photoelectric efficiency in perovskite photovoltaic cells, wherein Agent A is diluted with water 50-200 times and uniformly adhered to the surface or interior of photovoltaic glass with the assistance of a surfactant, forming a light absorption enhancement layer that improves the light absorption efficiency of the photovoltaic module. The agent B is uniformly coated on the surface of the photovoltaic electronic transmission component by atomization or sputtering, and after drying, it forms an electronic transmission enhancement layer that improves the electronic transmission efficiency of the photovoltaic module. The light absorption enhancement layer and the electron transport enhancement layer together form a photovoltaic composite layer that simultaneously improves photovoltaic photoelectric efficiency.
[0017] Compared with the prior art, the present invention has the following advantages and technical effects: This invention significantly improves the photoelectric performance of photovoltaic modules through the synergistic effect of Agent A and Agent B. Agent A, after plasma nitriding at 2500℃, forms a novel nitrogen-doped lattice, extending the light absorption response range to the full spectrum of 180nm~1500nm. When applied to LONGi Green Energy's 420mm×500mm photovoltaic glass, the average light absorption intensity across all wavelengths increases by 74%, and the light absorption coefficient is more than 20% higher than that of traditional crystalline silicon materials, effectively compensating for the insufficient light absorption capacity of traditional crystalline silicon. Agent B, through ultra-vacuum heating and high-temperature electric arc furnace discharge, forms a carbon atom recombination structure. When sputtered onto the perovskite light absorption layer, it increases the short-circuit current density by 60.8%, power generation by 49.82%, and conversion efficiency by 41.9%. When sputtered onto the electron transport layer (ETL), it increases the conversion efficiency by 16.58% and reduces the series resistance by 4.79%, solving the problem of poor electron transport in perovskite. The synergistic effect of the two agents achieves a closed loop of "increased light absorption - improved electron transport efficiency," significantly increasing the overall power generation of the photovoltaic module.
[0018] In terms of environmental protection and stability, the material of this invention does not contain lead ions or halide ions, thus avoiding the environmental hazards and corrosiveness of traditional photovoltaic materials. Furthermore, the nitrogen-doped lattice of agent A and the carbon atom recombination structure of agent B both have high stability. The specific surface area of agent A is more than 10 times higher than that before modification, and agent B can be dissolved in water or solvents, avoiding problems such as aging and agglomeration of traditional materials, and extending the service life of photovoltaic modules.
[0019] In terms of construction adaptability and application flexibility, both Agent A and Agent B are liquid mixtures. Agent A can be diluted with the aid of surfactants and then applied to the surface of photovoltaic glass or integrated into the glass manufacturing process through atomization, brushing, etc. Agent B can be applied to photovoltaic electronic transmission components through atomization and sputtering. It can be adapted to existing photovoltaic automated production lines without special equipment and can be applied to both crystalline silicon photovoltaic modules and perovskite photovoltaic cells, with a wide range of application scenarios.
[0020] Using these features, this invention provides an environmentally friendly composite material for improving photovoltaic photoelectric efficiency, along with its preparation method and application, which addresses the problems in existing technologies such as the inability of core photovoltaic materials to synergistically enhance light absorption and electron transmission efficiency, the presence of heavy metals / harmful ions and poor stability in traditional photovoltaic auxiliary materials, and the difficulty in adapting traditional auxiliary materials to existing photovoltaic production and application scenarios due to morphology / dispersion issues. Attached Figure Description
[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly described below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Figure 1 SEM images of agent A; Figure 2 EDS elemental photograph of agent A. Detailed Implementation
[0022] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0023] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0024] Example 1 This embodiment provides a method for preparing a material (Agent A) to improve light absorption: S1. Add 10 kg of titanium dioxide to a grinding mill, of which 50% is anatase titanium dioxide (5 kg) and 50% is rutile titanium dioxide (5 kg). Grind the mixture to 800 mesh, with a particle diameter of approximately 18 micrometers and a specific surface area of approximately 0.1 m². 2 / g~0.3m 2 / g.
[0025] S2. Add 20g of sodium sulfate to 10kg of 800-mesh titanium dioxide powder, add 100kg of water and disperse for 30 minutes. After 30 minutes, add 25g of sodium pyrophosphate and 5g of lanthanum chloride, mix and stir evenly for another 30 minutes, while simultaneously heating to 90 degrees Celsius until the moisture is dried.
[0026] S3. After drying, the powder is added to an electric arc furnace and heated by plasma at 2500 degrees Celsius for 1 hour. Sodium sulfate, sodium pyrophosphate, and lanthanum chloride or europium chloride are added to the titanium oxide. Nitrogen gas is then added to the titanium oxide under the high-temperature electric arc furnace plasma, generating active nitrogen atoms that activate the surface of the titanium oxide (TiO2). This replaces oxygen atoms on the surface or in the bulk phase with nitrogen atoms, forming a novel nitrogen-doped lattice titanium oxide. The lattice change results in a particle size below 50 nm and a specific surface area of approximately 20 m². 2 / g~50m 2 / g, cooled titanium oxide modified composite material is a cutting-edge material for light absorption, which can extend the response range of visible and invisible light from 180nm to 1400nm and improve the high sensitivity absorption response of light absorption.
[0027] The modified titanium dioxide, specifically the modified rare-earth titanium dioxide after nitriding, is a newly invented novel photovoltaic light-absorbing material.
[0028] S4. The prepared rare earth titanium oxide composite agent after nitriding is added to a 1 kg container at a ratio of 1%, deionized water is added and stirred evenly until the container is filled with 1 kg of water, and then the mixture is ground and mixed for 1 hour by a nano-grinding device. The resulting mixture is the light absorber A.
[0029] Sodium sulfate and sodium pyrophosphate are themselves excellent conductive agents. Here, they are used as light-conducting and transmission aids in light absorbers. During the production process, they react with titanium dioxide in the presence of lanthanum chloride or europium chloride catalysts to form a symbiotic reaction with the titanium dioxide lattice. Compared with titanium dioxide alone, they have stronger light absorption and light transmission dispersion and conduction capabilities during light absorption.
[0030] Lanthanum chloride or europium chloride is a photocatalytic aid that can promote and assist titanium dioxide in catalytically absorbing and converting invisible light into visible light.
[0031] Before modification, titanium dioxide can only absorb ultraviolet light. However, after the crystal lattice is changed, the modified titanium dioxide, with the help of photocatalytic agents such as lanthanum chloride or europium chloride, can maximize the expansion of the spectral absorption range, absorbing the spectral light source from 180nm to 1500nm under sunlight.
[0032] Depend on Figure 1 SEM images of enhanced light absorbers and Figure 2 The EDS elemental images show that the modified titanium dioxide lattice is significantly different from that of traditional titanium dioxide. Its lattice is finer and more evenly distributed, and its specific surface area is more than 10 times larger. The structural change improves the tunable bandgap spectral utilization rate by more than 10% and the light absorption coefficient by more than 20%. It has the potential to widely absorb and react with all light sources in the full spectrum.
[0033] Example 2 The only difference between this embodiment and Embodiment 1 is that lanthanum chloride is replaced with europium chloride.
[0034] Example 3 The only difference between this embodiment and Embodiment 1 is the ratio in step S4: In this embodiment, the prepared rare earth titanium oxide composite agent after nitriding is added to a 1 kg container at a ratio of 3%, deionized water is added and stirred evenly until the container is filled with 1 kg of water, and then the mixture is ground and mixed for 1 hour by a nano-grinding device. The resulting mixture is the light absorber A.
[0035] Example 4 The only difference between this embodiment and Embodiment 1 is the ratio in step S4: In this embodiment, the prepared rare earth titanium oxide composite agent after nitriding is added to a 1 kg container at a ratio of 5%, deionized water is added and stirred evenly until the container is filled with 1 kg of water, and then the mixture is ground and mixed for 1 hour using a nano-grinding device. The resulting mixture is the light absorber A.
[0036] Example 5 This embodiment provides a method for preparing a material (Agent B) to improve electron transport efficiency. S1. Add 10 kg of 800-mesh graphite to 50 g of dispersant polyethylene glycol, then add 20 g of sodium sulfate, 25 g of sodium pyrophosphate, 5 g of rubidium chloride, and 100 kg of water. Simultaneously heat to 60 degrees Celsius and perform ultrasonic mixing for 30 minutes. After 30 minutes, add 500 g of sulfuric acid for dissolution and oxidation treatment for 10 minutes, and then begin drying until the moisture is completely removed.
[0037] S2. The dried powder from step S1 is subjected to ultra-vacuum treatment (≤10). -6PA) is heated to 1300°C, cooled, and then placed in an electric arc furnace to discharge at over 3500°C for 30 minutes to form a carbon atom recombination-enhanced preliminary material for use.
[0038] S3. Add the powder produced by the electric arc furnace to isopropyl alcohol (IPA) at a ratio of 0.5% to 3%, and grind and mix it for 1 hour using a nano-ultrasonic grinding device.
[0039] S4. Finally, the mixture is dispersed by ultrasonic treatment to form a composite additive mixture with high electron transport efficiency for later use.
[0040] Sodium sulfate and sodium pyrophosphate are excellent conductive agents, and can be used here as an auxiliary and accelerating agent for graphene to act as an electron transport agent.
[0041] Rare earth rubidium is a highly efficient electron transport agent with a molecular weight of 120.92. It is used as a key power generation material in many aerospace applications. Rubidium chloride is an alkali metal halide, which is mainly used here to promote and help accelerate the electron transport efficiency of rare earth graphene produced in this study.
[0042] The graphene of this invention can be dissolved in water or solvent to form an aqueous solution or solvent after production, thus it can be easily constructed and applied without the problems of traditional graphene being powder or particles with excessively large particle size and uneven dispersion.
[0043] Example 7 This embodiment provides a method for improving the use of agent A, a light absorber material: S1: Take 1 kg of light absorber A stock solution, add commercially available cleaning surfactants (such as dodecylbenzene sulfonic acid or sodium dodecylbenzene sulfonate), then add deionized water to dilute the mixture 50 to 200 times, stir evenly to obtain the aqueous coating solution of agent A. S2: Select a photovoltaic crystalline silicon panel or perovskite photovoltaic glass to be processed (with no obvious damage to the outer surface), and use a tool that does not scratch the glass surface to evenly brush or coat the aqueous coating liquid of agent A prepared in step S1 onto the outer surface of the photovoltaic glass. S3: After coating, place the photovoltaic glass in a natural environment to allow the coating solution to dry naturally, or in a dusty outdoor setting, gently wash the glass surface with water to remove any remaining impurities, and then allow it to dry naturally. This ultimately forms a firmly adhered light absorption enhancement layer on the glass surface. This enhancement layer expands the light absorption response spectrum of the photovoltaic glass from ultraviolet light to the full spectrum, and its absorption coefficient is significantly lower than that of traditional crystalline silicon materials (10...). 3 cm -1 Increase by more than 20%.
[0044] Example 8 This embodiment provides a method for improving the use of agent A, a light absorber material: S1: In the raw material preparation stage of photovoltaic crystalline silicon glass production, according to the appropriate ratio of the total mass of photovoltaic glass raw materials to the light absorber A, add the light absorber A (in its original state) to the glass molten raw materials, stir evenly, and ensure that the light absorber A is uniformly dispersed in the glass raw materials; S2: The glass molten raw material containing agent A is fed into the conventional photovoltaic glass production process, and goes through melting, clarification, forming, annealing and other processes in sequence, so that agent A and crystalline silicon glass material can be fully combined during the high-temperature melting process; S3: After the glass is formed and cooled to room temperature, a new type of photovoltaic glass with built-in light absorber A is obtained. This glass does not require subsequent secondary coating treatment. Its light absorption response spectrum range has been extended from ultraviolet light to the full spectrum range. The light absorption coefficient is more than 20% higher than that of traditional crystalline silicon glass without A agent. It can be directly used for the encapsulation production of photovoltaic modules.
[0045] Example 9 This embodiment provides a method for improving the use of agent A, a light absorber material: S1: Take the stock solution of light absorber A, and dilute it with deionized water according to the application area on the inside of the photovoltaic glass (the dilution ratio is adjusted according to the standard of 50 to 200 times dilution of 1kg stock solution). After stirring evenly, the inner coating solution of agent A is obtained. S2: Select the photovoltaic glass before the photovoltaic module is encapsulated, fix it with the inside side facing up, and use manual brushing, automatic coating or sputtering to evenly apply the A agent inner coating liquid prepared in step S1 to the embossed particle surface of the glass inside, ensuring that the coating liquid covers the entire effective area of the glass inside. S3: After coating, place the glass in a temperature-controlled heater (the heater temperature is set to a normal drying temperature that does not affect the glass performance) and heat and dry until the coating liquid is completely cured, or allow it to dry naturally in a clean environment. Finally, a light absorption enhancement layer is formed on the inside of the glass. This enhancement layer can extend the light absorption response spectrum of the glass to the full spectrum, and the light absorption coefficient is increased by more than 20% compared with traditional crystalline silicon glass. The dried glass can be used for the normal encapsulation process of subsequent photovoltaic modules.
[0046] Example 10 This embodiment provides a method for using Agent B, a material for improving electron transport efficiency: Agent B, which improves electron transfer efficiency, is added at a ratio of 2% to 5% to photovoltaic components that require improved electron transfer efficiency (such as the transmission layer or passive layer of perovskite cells or any electron transfer component assembly in the process of transmitting light and electricity in photovoltaic crystalline silicon). Agent B is evenly distributed on the coating surface by means of solution atomization or sputtering. After brushing or coating evenly with auxiliary tools that do not scratch the glass surface, it can be naturally dried under natural conditions or thermally dried on an automated production line during the production of photovoltaic panels.
[0047] Experimental Example 1 This experimental example focuses on the performance study of photovoltaic glass with enhanced light absorption using light-absorbing agent A. By comparing the light intensity absorption data of photovoltaic glass before and after coating with agent A in different wavelength bands, the optimization effect of agent A on the full-spectrum absorption range is evaluated, specifically including: S1. Preparation of experimental materials: Materials for the experimental group: photovoltaic glass (420mm×500mm, with a certain ultraviolet absorption capacity) produced by LONGi Green Energy Technology Co., Ltd., and light-absorbing material A described in Example 1; Control group material: Blank photovoltaic glass of the same specifications and batch as the experimental group, without coating agent A; Auxiliary materials: Deionized water (for diluting agent A), sodium dodecylbenzenesulfonate (surfactant, used to enhance the adhesion of agent A).
[0048] Light source equipment: Commercially available simulated sunlight source (can simulate the full spectrum from 180nm to 1500nm, with light intensity stability error ≤ ±2%). Testing equipment: A commercially available spectrometer from Taiwan Advanced Micro Optics Co., Ltd., model number: SE2030-050-FUVN, spectral detection range: 180nm~1100nm, sensor: 2048 pixels, spectral collection software name: SpectraSmart, wavelength resolution ≤1nm), and a matching collimating lens (for accurately collecting the intensity of incident and transmitted light). Coating equipment: small atomizing sprayer (atomized particles with a diameter of 5~10μm to ensure uniform coating), soft silicone scraper (to avoid scratching the glass surface); S2. Preparation of test samples Sample preparation for the experimental group: Take 1 kg of light-absorbing material A stock solution, add 0.05 kg of sodium dodecylbenzenesulfonate, and then add deionized water to dilute to 100 kg (dilution ratio 100 times), stir evenly to obtain the A coating solution; use an atomizing sprayer to evenly spray the coating solution onto the outer surface of the photovoltaic glass of the experimental group, after spraying, gently scrape it smooth with a soft silicone scraper, and let it dry naturally for 24 hours to obtain the photovoltaic glass sample of the experimental group coated with A agent.
[0049] Preparation of control group samples: Blank photovoltaic glass was only cleaned (the surface dust was wiped off with deionized water and allowed to dry naturally before use), without the application of agent A, and served as the control group samples.
[0050] S3. Experimental setup The simulated solar light source, collimating lens, spectrometer, and photovoltaic glass sample were constructed as follows: Adjust the distance between the light outlet of the simulated sunlight source and the photovoltaic glass sample to 50cm to ensure that the light source shines on the glass surface at a straight angle. At the same time, fix the glass sample on the adjustable angle bracket so that the glass is at a 30-degree angle to the horizontal plane. A collimating lens (first collimating lens) is installed between the light source outlet and the glass sample to calibrate the incident light path and ensure that the light is perpendicular to the glass surface. A second collimating lens is installed 50 cm away on the other side (transmission side) of the glass sample, aligned with the spectrometer detection port, to collect the light signal transmitted through the glass and transmit it to the spectrometer.
[0051] S4, Light Intensity Detection The detection parameters are set through the spectrometer control software: the detection band is 180nm~1100nm, each 10nm is a detection node, each node is detected 3 times continuously, and the average value is taken as the light intensity detection value of the band. The detection program was started, and the light intensity signals transmitted through the glass of the experimental group and control group samples were collected using a collimating lens. The spectrometer automatically recorded the data for each band. After the detection was completed, the data was exported to the analysis software, and the light intensity difference value for each band was calculated (difference value = (experimental group light intensity - blank group light intensity) / blank group light intensity × 100%). The specific data are shown in the table below:
[0052] Data analysis showed that the light intensity absorption values of the photovoltaic glass in the experimental group were significantly higher than those in the control group in all wavelength bands. The light intensity improvement rate was the highest in the 440nm~485nm band (91.5%), and the average light intensity improvement was 74% in the 180nm~1100nm band. This verified that the light absorption material A can effectively expand the light absorption range of photovoltaic glass and improve the full-spectrum absorption efficiency.
[0053] Experimental Example 2 This experiment was conducted to verify the effect of electron transport efficiency material B on improving the electron transport efficiency and photoelectric conversion performance of tandem perovskite solar cells, and to discuss the performance changes of B when sputtered onto the perovskite light absorption layer (methylammonium lead iodide, MAPbI3 layer).
[0054] S1. Material and Equipment Preparation Tandem perovskite solar cells: Unencapsulated tandem perovskite solar cells prepared in the same batch (the main material of the light absorption layer is methylammonium lead iodide MAPbI3). Agent B: A mixture of high electron transport efficiency composite additives prepared according to the process in Example 5; Coating equipment: Small vacuum sputtering machine (vacuum degree ≤10) -4 Pa, sputtering rate 0.1~0.5 nm / s); Testing equipment: Commercially available photovoltaic cell performance tester (capable of testing parameters such as Jsc, Voc, W, FillFactor, η, etc., with a testing accuracy of ≤±1%). Cleaning equipment: dust-free wiping cloths, small ultrasonic cleaners.
[0055] S2. Grouping and Preparation of Test Samples Control group sample: One stacked perovskite solar cell was selected, its surface was wiped with anhydrous ethanol, and then cleaned by ultrasonic cleaner (300W power, 2min time). After natural drying, it served as the control group sample without the application of agent B.
[0056] Experimental group sample: One tandem perovskite solar cell from the same batch was selected, cleaned as the control group, and placed in a vacuum sputtering machine; 3.5% of the B-type stock solution was taken, and the sputtering parameters were set (vacuum degree 5×10). -5 At a sputtering rate of 0.3 nm / s (Pa), agent B was uniformly sputtered onto the surface of the MAPbI3 light-absorbing layer. After sputtering, the sample was removed and allowed to cool naturally to room temperature, serving as the experimental group sample using agent B.
[0057] S3. Test Environment and Equipment Calibration The photovoltaic cell performance tester was placed in a constant temperature and humidity environment of 25℃ and 40% relative humidity for 30 minutes for preheating; a standard calibration cell was used (known parameters: Jsc = 15mA / cm). 2 The tester was calibrated (Voc=900mV) to ensure accurate test data.
[0058] S4, Performance testing of the control group The control group tandem perovskite solar cell was fixed on the sample stage of the tester, aligned with the test probe, and the test program was started. The test was performed three times in a row, and the short-circuit current density (Jsc), open-circuit voltage (Voc), power generation (W), fill factor (FillFactor), and conversion efficiency (η) were recorded. The average value was taken as the control group data.
[0059] S5, Experimental Group Performance Testing Keeping the instrument parameters unchanged, replace it with the experimental group's tandem perovskite solar cell, repeat the detection steps in S4, and perform the same detection 3 times and take the average value. Record the experimental group data.
[0060]
[0061] Compared with the control group, the experimental group of batteries showed an increase of over 60.8% in short-circuit current density (Jsc), nearly 50% in power generation (W), and over 40% in conversion efficiency (η), verifying that agent B can effectively accelerate electron transport in the MAPbI3 layer and reduce electron recombination losses.
[0062] Experimental Example 3 S1. Grouping and Preparation of Test Samples Experimental group: The finished product of material B for improving electron transport efficiency was added at a ratio of 3.5% to the electron transport layer (ETL) sheet of the tandem perovskite solar cell material.
[0063] Control group: Batteries without an electron transport layer (ETL) coating (without agent B).
[0064] S2, Performance testing at room temperature (25℃) The photovoltaic tester was calibrated, and the two sets of cells were fixed on the test stand to test their performance.
[0065] The experimental results are shown in the table below:
[0066] As shown in the table above, after agent B is sputtered onto the ETL layer, the battery conversion efficiency at room temperature is increased by 16.58%, the short-circuit current is increased by 12.5%, the conversion efficiency is increased by 16.58%, the series resistance is reduced by 4.79%, and the parallel resistance is increased by 27.69%, proving that agent B can simultaneously improve electron transport efficiency and temperature stability.
[0067] Test Example 4 This experimental example investigates the performance of photovoltaic modules when agent A and agent B are used in combination: Commercially available photovoltaic glass was coated with the light-absorbing material A agent of Example 1 provided by the present invention, and the electron transmission efficiency material B agent of Example 5 was sputtered onto the perovskite light-absorbing layer to prepare a set of 650W photovoltaic modules, which were placed outdoors together with a set of uncoated 650W photovoltaic modules.
[0068] Light exposure experiment: 5 hours of effective time. The combined effect of the products was verified under the same environmental conditions, temperature and placement angle. Since the photovoltaic glass is integrated with the module, it is not possible to test the light absorption efficiency separately for comparison. Therefore, the power generation efficiency was used for evaluation and analysis.
[0069] As shown in the table below, the photovoltaic power generation efficiency increases significantly by more than 10% after applying agent A and agent B to photovoltaic modules.
[0070]
[0071] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. An environmentally friendly composite material for improving photovoltaic photoelectric efficiency, characterized in that, The composite material consists of Agent A, which is used to improve the light absorption efficiency of photovoltaic modules, and Agent B, which is used to improve the electron transport efficiency of photovoltaic modules. Agent A is titanium oxide, sodium sulfate, sodium pyrophosphate, and rare earth compounds that are ground and then subjected to nitriding treatment under plasma heating at 2500℃ with nitrogen gas to form a nitrogen-doped lattice, which is then dissolved in deionized water and nano-grinded to obtain the product. The rare earth compound is a rare earth chloride or a rare earth acetate compound. The agent B consists of graphite, polyethylene glycol, sodium sulfate, sodium pyrophosphate, a rubidium-containing soluble ionic salt, and sulfuric acid. After ultrasonic mixing and oxidation, a graphite product is formed, with a concentration ≤10. -6 The carbon atom recombination structure is formed by heating at 1300℃ under ultra-vacuum and then being discharged in an electric arc furnace at 3500℃. Finally, it is dissolved in isopropanol and then prepared by nano-ultrasonic grinding. The rubidium-containing soluble ionic salt is rubidium chloride or rubidium acetate.
2. The environmentally friendly composite material for improving photovoltaic photoelectric efficiency according to claim 1, characterized in that: The titanium oxide in Agent A is composed of anatase titanium oxide and rutile titanium oxide, and the mass ratio of anatase titanium oxide to rutile titanium oxide is 1:
1. The titanium dioxide accounts for 1% to 5% of the total mass of agent A.
3. The environmentally friendly composite material for improving photovoltaic photoelectric efficiency according to claim 1, characterized in that: The rare earth compound in Agent A is lanthanum chloride or europium chloride.
4. The environmentally friendly composite material for improving photovoltaic photoelectric efficiency according to claim 1, characterized in that: The mass ratio of titanium dioxide, sodium sulfate, sodium pyrophosphate, and rare earth chloride in Agent A is 10000:20:25:
5.
5. The environmentally friendly composite material for improving photovoltaic photoelectric efficiency according to claim 1, characterized in that: The mass ratio of graphite, polyethylene glycol, sodium sulfate, sodium pyrophosphate, rubidium chloride, and sulfuric acid in Agent B is 10000:50:20:25:5:
500.
6. The environmentally friendly composite material for improving photovoltaic photoelectric efficiency according to claim 1, characterized in that: The mass ratio of isopropanol to graphite product in agent B is 100:0.5-3.
7. A method for preparing the environmentally friendly composite material for improving photovoltaic photoelectric efficiency as described in any one of claims 1-6, characterized in that, include: S1. Titanium oxide pretreatment: Anatase titanium oxide and rutile titanium oxide are mixed in a mass ratio of 1:1 and ground to 800 mesh to obtain titanium oxide mixed powder; S2. Dispersion and doping: Sodium sulfate, sodium pyrophosphate and rare earth chloride are added to the titanium dioxide mixed powder, dispersed with water and then dried to obtain a dry powder. S3. High-temperature nitriding modification: The dried powder is placed in an electric arc furnace and nitrided by introducing nitrogen gas under plasma heating conditions at 2500℃ to form nitrogen-doped lattice powder. S4. Preparation of finished product: The nitrogen-doped lattice powder is added to deionized water at a ratio of 1% to 5% of the total mass of the final agent A, and then ground to obtain agent A; S5. Graphite pretreatment and oxidation: Add 800-mesh graphite to polyethylene glycol, sodium sulfate, sodium pyrophosphate, rubidium chloride and water, then add sulfuric acid for oxidation, let stand and dry to obtain dry powder; S6. High-temperature recombination: The dried powder is heated at ≤10°C. -6 Heating to 1300℃ under ultra-vacuum conditions, cooling and then placing in an electric arc furnace and discharging at above 3500℃ yields carbon atom recombinant powder. S7. Solvent mixing and dispersion of the finished product: The carbon atom recombinant powder is added to isopropanol at a ratio of 0.5% to 3% of the total mass of the final agent B, and then subjected to nano-ultrasonic grinding and ultrasonic dispersion to obtain agent B.
8. The method for preparing an environmentally friendly composite material to improve photovoltaic photoelectric efficiency according to claim 7, characterized in that: In the nitriding process of step S3, the heat preservation reaction time is 0.8-1.2h.
9. The method for preparing an environmentally friendly composite material to improve photovoltaic photoelectric efficiency according to claim 7, characterized in that: In step S6, during the discharge process at temperatures above 3500°C, the discharge time is 25-35 minutes.
10. The application of an environmentally friendly composite material for improving photovoltaic photoelectric efficiency according to any one of claims 1-6 in perovskite photovoltaic cells, characterized in that: The agent A is diluted with water 50-200 times and then uniformly adhered to the surface or interior of the photovoltaic glass with the assistance of a surfactant to form a light absorption enhancement layer that improves the light absorption efficiency of the photovoltaic module. Agent B is uniformly coated onto the surface of the photovoltaic electronic transmission component by atomization or sputtering, and after drying, it forms an electronic transmission enhancement layer that improves the electronic transmission efficiency of the photovoltaic module. The light absorption enhancement layer and the electron transport enhancement layer together form a photovoltaic composite layer that simultaneously improves photovoltaic photoelectric efficiency.
